Relationship between laboratory-measured variables and heart rate during an ultra-endurance triathlon - Laursen, P. B.; Knez, W. L.; Shing, C. M.; Langill, R. H.; Rhodes, E. C.; Jenkins, D. G. (Journal of Sports Sciences, 2005)
The aim of the present study was to examine the relationship between the performance heart rate during an ultra-endurance triathlon and the heart rate corresponding to several demarcation points measured during laboratory-based progressive cycle ergometry and treadmill running. Less than one month before an ultra-endurance triathlon, 21 well-trained ultra-endurance triathletes (mean±s: age 35±6 years, height 1.77±0.05m, mass 74.0±6.9kg, =4.75±?0.42l.min-1) performed progressive exercise tests of cycle ergometry and treadmill running for the determination of peak oxygen uptake (VO2peak), heart rate corresponding to the first and second ventilatory thresholds, as well as the heart rate deflection point. Portable telemetry units recorded heart rate at 60?s increments throughout the ultra-endurance triathlon. Heart rate during the cycle and run phases of the ultra-endurance triathlon (148±9 and 143±13 beats·min-1 respectively) were significantly (P<0.05) less than the second ventilatory thresholds (160±13 and 165±14 beats·min-1 respectively) and heart rate deflection points (170±13 and 179±9 beats·min-1 respectively). However, mean heart rate during the cycle and run phases of the ultra-endurance triathlon were significantly related to (r=0.76 and 0.66; P<0.01), and not significantly different from, the first ventilatory thresholds (146±12 and 148±15 beats?·?min-1 respectively). Furthermore, the difference between heart rate during the cycle phase of the ultra-endurance triathlon and heart rate at the first ventilatory threshold was related to marathon run time (r=0.61; P<0.01) and overall ultra-endurance triathlon time (r=0.45; P<0.05). The results suggest that triathletes perform the cycle and run phases of the ultra-endurance triathlon at an exercise intensity near their first ventilatory threshold.